PROFIL GURU MENGENAI PEMAHAMAN GAYA BELAJAR PESERTA DIDIK DI SDN 15 SEGEDONG - Afkarina, Iza; Yunika Afryaningsih, Yuyun (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe teachers’ understanding of students’ learning styles at SDN 15 Segedong, particularly visual, auditory, and kinesthetic (VAK) learning styles. A qualitative approach was employed, using focused interview methods with homeroom teachers from grades I to VI as informants. Data were collected through direct interviews and analyzed descriptively. The results show that teachers at SDN 15 Segedong have varying levels of understanding regarding students’ learning styles. The visual learning style is the most recognized and understood by teachers, as it is easier to implement using media such as images, videos, and diagrams. Meanwhile, auditory and kinesthetic learning styles are not yet fully understood by all teachers. Teachers who understand the auditory style tend to use discussions, oral explanations, and audio as learning media. For kinesthetic learners, teachers rely on physical activities such as experiments, educational games, and outdoor learning.